Modification of the jig slider grinding hook design - Andaresta, Windy; Purba, Adi Syahputra; Yuniarsih, Nidia; Marbun, Abri Andry Saresa; Saputra, Rangga (International Journal of Mechanical Computational and Manufacturing Research, 2025)
Tools such as jigs are becoming important in the production process. Jigs are often used in the cutting or shaping process in the form of making workpieces in production. However, ever-changing variations in demand can lead to changes in jig efficiency. Therefore, modifications are necessary to maintain accuracy and meet the demands of diverse markets. This research was carried out by modifying the design of the slider jig on the width of the rail slider which was enlarged from before and adding support to the clamping plate which aims to improve the accuracy and effectiveness in the drilling process. To find out the results of the difference before and after the modification of the slider jig, a test was carried out by conducting a visual inspection of the profile point hook that had been ground using a profile projector with a scale of 10 :1 which showed that the results of this modification were included in the value of the drawing tolerance value and in accordance with the specifications in the company and based on data taken from PT. XYZ in the engine working time of 3 hours and 3 minutes, a total output of 164 pcs was found out of the total target of 158 pcs. This resulted in a productivity percentage of 103.80%. This shows that this jig modification is effective when used.